Erling Kristvik en nasjonal strateg? - Madssen, Kjell-Arild (Kyrkjefag Profil, 2020)
Erling Kristvik (1882-1969) was a central figure in the Norwegian educational system in the 20th century. He was known for being the principle of Volda University College from 1930, as well as a writer of textbooks for teacher education. This book centers around Kristviks authorship, focusing on a manuscript many thought to be lost: Folkelære. Pedagogisk sosiologi, written in the 1940s and the key point of analysis in this book, was never published.